A comparative study on in vitro degradation behavior of PLLA-based copolymer monofilaments. (December 2018) - Shi, Daokun; Kang, Yahong; Zhang, Guoyi; Gao, Chenguang; Lu, Wei; Yang, Caihong; Zou, Hua; Jiang, Hongyan
Abstract: Three kinds of high molecular weight polymers were synthesized by ring-opening polymerization with various monomer feeding ratios (named as PLLA, PLCL 95/5 and PLGC 80/15/5, respectively). Then oriented monofilament was produced through melt-extrusion and tensile orientation based on each kind of polymer. In vitro degradation properties of the monofilaments were studied over a range of degradation time from 1 to 21 days at 60 °C by using SEM, GPC, DSC, XRD and tensile test. Degradation results showed that the mass loss, T g and morphology integrity of the PLLA monofilament basically remained unchanged, and partial degradation in amorphous region emerged with slight increase of crystallinity. For the PLCL 95/5 monofilament, the crystallinity was increased and the monofilament was fractured at 14 days accompanying with obvious decrease of the mass and T m, indicating that most part of the amorphous region was degraded. Apparently, the PLGC 80/15/5 monofilament showed the fastest degradation rate with considerable mass loss and decrease of T g . The amorphous region was degraded sharply in the early stage due to its good water absorbability and lower structural regularity, and the initially-formed crystalline region was degraded slowly later evidenced from the change of crystallinity and it was fractured at 3 days. The accelerated effects calculated according to the first-order kinetic model demonstrated that the PLCL 95/5 monofilament was degraded 2.5 times faster than pure PLLA and the PLGC 80/15/5 monofilament was degraded 7.5 times faster than PLLA. These were nearly consistent with those based on [ η ] (2.5 and 6.9 times respectively). The comparative study of in vitro degradation behavior of PLLA-based copolymer monofilaments would provide useful information for controlling the monomer composition of PLLA-based materials with specific degradation requirements. Highlights: Three kinds of high molecular weight polymers were synthesized with various monomer feeding ratios. A comparative study of in vitro degradation behavior of the PLLA-based copolymer monofilaments was conducted. The PLGC 80/15/5 monofilament showed the most rapid degradation behavior owning to its higher hydrophilicity. The accelerated effects were applied to analyze the relationship between the monomer ratio and the degradation rate.